Continuous Analgesia with Intercostal Catheterization after Thoracoscopy - Wang, Yifei; Sun, Qi; Huang, Yiling; Yang, Qinghua; Chen, Rong; Zhang, Xianwei; Zhao, Xuewei; Wang, Mingdong (The Thoracic and Cardiovascular Surgeon, 2023)
Background There are few studies on continuous intercostal nerve block after single operation hole thoracoscopic surgery, that is, two-port thoracoscopic surgery.Objective To evaluate the analgesic effect of continuous intercostal nerve block after thoracoscopic surgery.Methods A total of 80 patients who underwent single operation hole thoracoscopic surgery in our hospital between September 2020 and June 2021 were enrolled and divided into two groups. Based on basic analgesia, an intercostal catheter was placed during the operation for continuous intercostal block analgesia after the operation in the experimental group (group A, n = 40). The control group (group B, n = 40) was treated with sufentanil intravenous analgesia after surgery, which is namely “basic analgesia.” The postoperative pain scores, restlessness during the recovery period, effect on reducing opioid use, postoperative chest complications, patient satisfaction, etc., were compared between the two groups.Results The pain scores of patients in group A were significantly lower compared with those in group B at 12, 24, 36, and 48 hours after surgery (3.325 ± 1.163 vs. 4.550 ± 1.176, 2.650 ± 1.001 vs. 4.000 ± 1.038, 2.325 ± 0.917 vs. 3.700 ± 0.966, and 1.775 ± 1.050 vs. 3.150 ± 1.075, p < 0.001, respectively). Sufentanil consumption in group A was significantly lower than in group B at 48 hours after surgery (98.625 ± 4.158 vs. 106.000 ± 7.228, p < 0.001).Conclusion Multimodal analgesia is ideal for early pain control after thoracotomy. A continuous intercostal nerve block can effectively reduce postoperative pain in patients.
Keywords: thoracoscopy/VATS; postoperative; lung; treatment